Training processes of World Masters Orienteering Championship medalists - Piotr Cych; Weronika Machowska-Krupa (PLoS ONE, 2025)
The study aimed to capture the relationships between sports performance and workouts in different foot orienteer age groups. The preparation process of 49 World Masters Orienteering Championship (WMOC) medalists (aged 35–75) was surveyed using a questionnaire. The respondents were asked about the number of training sessions, time devoted to training and competitions, and the characteristics of the training measures used (including the number of specialized training sessions and competitions) during the preparation and competition periods. The data underwent non-parametric statistical analysis, with the Mann-Whitney U test used to assess differences between two structural indicators. Men trained more frequently than women (p = 0.015), and younger subgroups (WM35-WM55) trained more often than older ones (WM60-WM75) (p = 0.021). During preparation, men trained longer than women (p = 0.045), while younger masters trained more hours than older ones. No significant gender differences were found in training volume during the competition period (p = 0.74). Sixty-two percent of medalists used over 10 specialized training sessions within six months of WMOC, with younger male veterans (M35-M55) reporting the highest number. More men (92.9%) than women (54.5%) competed over 10 times in the six months preceding WMOC (p = 0.002). WMOC medalists trained optimally, considering age-related decline, and frequently prepared by participating in orienteering competitions. Some training work-out differences were observed among medalists based on age and sex. The study observations provide the first insight into the preparation of master category orienteering competitors for international competition. Indeed, most are very professional in their preparation and devote much time to training and participating in competitions, especially younger competitors.